PENGARUH DISIPLIN KERJA DAN LINGKUNGAN KERJA TERHADAP KINERJA PEGAWAI PADA KANTOR KECAMATAN SUKAMULYA KABUPATEN TANGERANG - Felicia Balqis Izza; Tjeri Hadjrillah (Journal of Research and Publication Innovation, 2025)
The purpose of this study is to determine the influence of Work Discipline and Work Environment on Employee Performance at the Sukamulya District Office, Tangerang Regency. The method used is the Quantitative method. The sampling technique used saturated samples and a sample of 48 respondents was obtained. Data analysis uses validity tests, reliability tests, classical assumption tests, regression analysis, correlation coefficients, determination coefficients and hypothesis tests. The results of this study are that Work Discipline has a significant effect on Employee Performance with a determination coefficient value of 70.5% and the hypothesis test is obtained by calculating t > t table or (2,334> 1,661). The Work Environment has a significant effect on Employee Performance with a determination coefficient value of 64.0% and the hypothesis is obtained t calculation > t table or (18.968 > 1.661). Work discipline and work environment simultaneously have a significant effect on Employee Performance with the regression equation Y= 8.151+ 0.632X1 with a significance value of 0.000 < 0.05.